New shock microstructures in titanite (CaTiSiO5) from the peak ring of the Chicxulub impact structure, Mexico - Timms, Nick; Pearce, M.A.; Erickson, Timmons; Cavosie, Aaron; Rae, A.S.P.; Wheeler, J.; Wittmann, A.; Ferrière, L.; Poelchau, M.H.; Tomioka, N.; Collins, G.S.; Gulick, S.P.S.; et al. (SPRINGER, 2019)
Accessory mineral geochronometers such as apatite, baddeleyite, monazite, xenotime and zircon are increasingly being recognized for their ability to preserve diagnostic microstructural evidence of hypervelocity-impact processes. To date, little is known about the response of titanite to shock metamorphism, even though it is a widespread accessory phase and a U–Pb geochronometer. Here we report two new mechanical twin modes in titanite within shocked granitoid from the Chicxulub impact structure, Mexico. Titanite grains in the newly acquired core from the International Ocean Discovery Program Hole M0077A preserve multiple sets of polysynthetic twins, most commonly with composition planes (K1) = ~ { 1 ¯ 11 } , and shear direction (η1) = < 110 > , and less commonly with the mode K1 = {130}, η1 = ~ <522 >. In some grains, {130} deformation bands have formed concurrently with the deformation twins, indicating dislocation slip with Burgers vector b = < 341 > can be active during impact metamorphism. Titanite twins in the modes described here have not been reported from endogenically deformed rocks; we, therefore, propose this newly identified twin form as a result of shock deformation. Formation conditions of the twins have not been experimentally calibrated, and are here empirically constrained by the presence of planar deformation features in quartz (12 ± 5 and ~ 17 ± 5 GPa) and the absence of shock twins in zircon (< 20 GPa). While the lower threshold of titanite twin formation remains poorly constrained, identification of these twins highlight the utility of titanite as a shock indicator over the pressure range between 12 and 17 GPa. Given the challenges to find diagnostic indicators of shock metamorphism to identify both ancient and recent impact evidence on Earth, microstructural analysis of titanite is here demonstrated to provide a new tool for recognizing impact deformation in rocks where other impact evidence may be erased, altered, or did not manifest due to generally low (< 20 GPa) shock pressure.